Bixin protects against particle-induced long-term lung injury in an NRF2-dependent manner. Issue 2 (2nd February 2018) - Xue, Lian; Zhang, Hong; Zhang, Jie; Li, Bingyan; Zhang, Zengli; Tao, Shasha
Abstract : Scope : Particle-induced lung injury is a kind of comprehensive pulmonary disease with not only inflammation but also fibrosis. Abstract : Scope : Particle-induced lung injury is a kind of comprehensive pulmonary disease with not only inflammation but also fibrosis. Bixin is a natural compound that is widely used as a food additive. Our previous studies demonstrated that bixin could alleviate inflammation in ventilation-induced acute lung injury as well as UV-exposure caused skin damage. But whether it could depress silica-induced long-term comprehensive lung injury and the mechanism of bixin in this protection have not yet been studied. Methods : A murine SiO2 -induced long-term comprehensive lung injury model was established through silica intratracheal instillation. To elucidate the effects and mechanisms of bixin in silica-induced pulmonary inflammation and fibrosis, we treated mice with bixin following silica instillation. Results : Bixin treatment attenuated the accumulation of inflammatory cells which significantly ameliorated pathological inflammation and fibrotic development in the lungs. In addition, intraperitoneal (i.p.) injection of bixin in mice led to the upregulation of the NRF2 response in the lungs. Since alveolar macrophage activation plays a vital role in the initiation and progression of this injury, the mechanism was further studied in the THP-1 macrophage cells. Bixin activated NRF2 signals via blocking KEAP1 mediated ubiquitylation and degradation of NRF2. Conclusions : Our work has brought insights into exploring anti-particle-induced lung injury activities in the daily consumption of natural products. In addition, our study also inspires the discovery of new beneficial effects of bixin and its application in the treatment of other inflammatory diseases.